Inverse Association between Platelet-to-Lymphocyte Ratio and Clinical Severity in Pediatric Dengue Infection: A Retrospective Cross-Sectional Analysis at Wangaya Hospital, Indonesia - Desak Agung Indah Praharsini Dewi; I Gusti Ayu Wiradari Tedja; Made Ayu Vita Prianggandanni (Archives of The Medicine and Case Reports, 2026)
Dengue heavily burdens endemic regions. Early prediction of disease progression in pediatric populations is critical for optimizing outcomes. This study evaluates the Platelet-to-Lymphocyte Ratio (PLR), an emerging inflammatory marker, as a correlative biomarker of clinical severity in pediatric dengue. A retrospective cross-sectional analysis included 139 pediatric patients with confirmed dengue at Wangaya Regional General Hospital, Denpasar, Indonesia. Patients were classified using 2009 World Health Organization criteria into Dengue Fever (DF), Dengue with Warning Signs (DWS), and Severe Dengue (SD). Hematological parameters were obtained strictly during the critical transition phase. Statistical analyses included Kruskal-Wallis tests, Spearman correlation, Receiver Operating Characteristic (ROC) curve analysis, and Ordinal Logistic Regression. The cohort, primarily school-aged children (92.1%), presented with 11.5% DF, 73.4% DWS, and 15.1% SD. A statistically significant, weak-to-moderate inverse correlation existed between the admission PLR and clinical severity (r = -0.293, p < 0.001). The median admission PLR declined progressively from 78.1 in DF, to 59.8 in DWS and further to 24.3 in SD. ROC analysis discriminating Severe Dengue yielded an Area Under the Curve of 0.685. Regression confirmed the PLR as an independent, modest correlative factor when adjusting for age, sex, and fever onset day. In conclusion, a statistically significant, weak-to-moderate inverse association exists between admission PLR and pediatric dengue severity. While offering accessible pathophysiological insights, its moderate diagnostic accuracy limits its use as an isolated triage tool. The PLR may assist early risk stratification in resource-limited settings when utilized alongside standard clinical assessments.